2019
DOI: 10.1038/s41568-019-0183-z
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis checkpoints as new targets for cancer immunotherapy

Abstract: Cancer immunotherapies that target adaptive immune checkpoints have significantly improved patient outcomes for multiple metastatic and treatment-refractory cancers. Recent studies, however, have demonstrated that innate immune checkpoints, which interfere with the detection and clearance of malignant cells and suppress innate sensing, also play a critical role in tumourmediated immune escape and may be potential targets for cancer immunotherapy. In this review, we highlight the current understanding of how ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
557
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 644 publications
(614 citation statements)
references
References 232 publications
5
557
0
1
Order By: Relevance
“…Kong X et al reported that the LPS-induced downregulation of Sirpα contributed to innate immune activation in macrophages. 19 Lin Y et alclaimed that notch signaling The survival of the mice described above in (a) is shown (n = 10, ***P < 0.005; ns, not significant; Gehan-Breslow-Wilcoxon test). c The Elk-1 transgene prevented Ap-2α silencing-induced tumor phagocytosis.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Kong X et al reported that the LPS-induced downregulation of Sirpα contributed to innate immune activation in macrophages. 19 Lin Y et alclaimed that notch signaling The survival of the mice described above in (a) is shown (n = 10, ***P < 0.005; ns, not significant; Gehan-Breslow-Wilcoxon test). c The Elk-1 transgene prevented Ap-2α silencing-induced tumor phagocytosis.…”
Section: Discussionmentioning
confidence: 98%
“…28,29 To date, research has mainly focused on improving adaptive immune functions, but recent studies have indicated that the Sirpα-CD47 pathway, a phagocytosis checkpoint in macrophages and other innate immune cells, may be an interesting therapeutic target. 17,19,22 Recent strategies for the blockade of the Sirpα-CD47 axis mainly rely on antibodies. 13,17 Here, we focused on the regulatory mechanism underlying SIRPα expression and identified two upstream transcription factors, Ap-2α and ELK-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibiting the CD47-SIRPα interaction promotes the phagocytosis of tumor cells, which can be achieved therapeutically using anti-CD47 or anti-SIRPα antibodies. In the clinical setting, CD47-SIRPα axis blocking agents are nowadays being evaluated in many clinical trials, either as monotherapies or in combination therapies (Table 2) [175]. In vitro, dual blockade of the PD-1-PD-L1 axis and CD47-SIRPα induced immune cell activation and suppressed tumor growth and metastases in a mouse xenograft model.…”
Section: Phagocytosis Checkpoint Inhibitorsmentioning
confidence: 99%